(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
On September 2021, the ECtHR has delivered its first-ever decision on a request for an advisory opinion under art. 29 of the Oviedo Convention. The ECtHR has established – giving a strict interpretation of the limits of its advisory jurisdiction – that the request is not within its competence ratione materiae. The present paper aims at analyzing the decision deepening the theoretical framework the Court offered about its advisory jurisdiction, focusing on the similarities and differences among the ECHR’s advisory opinion mechanisms, and providing food for thought about the contextualization of this decision within the ECtHR’s constitutionalisation process.